Response of organic matter pore development to functional groups in overmature marine shale: Insights from AFM-IR spectroscopy - Jianhua ZHAO; Keyu LIU; Shenghui ZHAO; Qinhong HU; Wei WU; Yang CHEN; Guoheng LIU; Junqian LI; Lingjie YU; Zuhui YOU; Ye WANG (Petroleum Exploration and Development)
Taking the Lower Silurian Longmaxi Formation shale in the Sichuan Basin as an example, this study employs atomic force microscopy-based infrared (AFM-IR) spectroscopy to analyze the submicron-scale molecular functional groups of different types and occurrences of organic matter. Combined with the quantitative evaluation of pore development via scanning electron microscopy (SEM), the response of organic pore formation and evolution mechanisms to chemical composition and structural evolution of organic matter in overmature marine shale is investigated. The results indicate that the AFM-IR spectra of graptolite periderms and pyrobitumen in shale are dominated by the stretching vibrations of conjugated C=C bonds in aromatic compounds at approximately 1 600 cm-1, with weak absorption peaks near 1 375, 1 450 and 1 720 cm-1, corresponding to aliphatic chains and carbonyl/carboxyl functional groups. Overall, the AFM-IR structural indices (A and C factors) of organic matter show a strong correlation with visible porosity in shales of equivalent maturity. Lower A and C factor values correlate with enhanced development of organic pores, which is associated with the detachment of more aliphatic chains and oxygen-containing functional groups during thermal evolution. Pyrobitumen-clay mineral composites generally exhibit superior pore development, likely attributable to clay mineral dehydration participating in hydrocarbon generation reactions that promote the removal of more functional groups. Additionally, hydrocarbon generation within organic-clay composites during high–over mature stages may induce volumetric expansion, resulting in microfracturing and hydrocarbon expulsion. The associated higher hydrocarbon expulsion rates promote the formation of larger pores and fracture-shaped pores along the flake-shaped clay minerals. This study highlights that the research of submicron-scale molecular functional groups provides a deeper understanding of organic matter evolution and pores development mechanisms in overmature shales, thereby offering critical theoretical parameters for reservoir evaluation in shale oil and gas exploration.